A retrospective descriptive analysis of prehospital advanced airway management in a South African private emergency medical service - Araie, Farzana (Department of Anaesthesia and Perioperative Medicine, 2022)
Introduction: Emergency medical systems have evolved from mostly providing patient transport to healthcare facilities to the provision of emergency care interventions on scene or en route to a healthcare facility. Endotracheal intubation is one of these interventions but despite being performed in the prehospital setting for nearly two decades, the practice of prehospital ETI has not yet been examined on a national level. Methods: This is a retrospective chart review of prehospital ETI performed by non-physician prehospital providers of a ground-based emergency medical service that operates on a national level over a 12 month period. Results: Of the 806 cases recorded in the study period, 683 met the criteria for analysis. Male patients accounted for 67% of the cases. The majority of patients (56%) intubated were trauma patients while the remaining 44% were intubated for medical reasons. The first pass success rate was 74% and the overall success rate was 98%. Rapid sequence intubation was the method used to intubate 34% of patients. Approximately 29% received drug facilitated intubation and 27% of patients were intubated whilst being treated for cardiac arrest. Approximately 65% of patients had documented risk factors for difficult intubation. Clinical adverse events were recorded in 14% of cases. Discussion: The first pass success and overall success rates compare favourably with those reported in similar contexts. Adverse events were thought to be under-reported.